Women's Participation in The Selection of Contraceptive Methods – Knowledge, Attitude and Culture - Amaral, Meriana Barreto (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Timor Leste is one of the developing countries with one of the main problems faced is the population sector, namely the high rate of population growth. The purpose of this study is for what factors influence the knowledge, attitudes and culture of women to participate in the selection of contraceptive methods at the Formosa Health Center. This research method is carried out descriptively with a quantitative approach. The population of this study was Women of reproductive age who sought family planning services at the Formosa Health Center. The results of this study revealed that most participants or women sought family planning services at the Formosa Health Center, dominated by women from the age group of 20 to 24 years and with a higher level of education. We found that there was little information regarding the type of use and source of information, participants with knowledge and level of education preferred to use artificial methods, especially the most widely used ones were Injections, compared to Pills, IUD and Implant. It is highlighted that the side effects of the injection contraceptive method are dizziness and headache. However, there is no fundamental reason to stop use. It is emphasized that only a quarter of women have the knowledge that the advantage of using contraceptives is only to prevent pregnancy.